Secretion of inflammatory mediators by human intestinal epithelial cells incubated with gastric digesta of emulsion gels containing capsaicinoids: Implication on gastric irritation - Luo N; Wolber FM; Singh H; Ye A (Elsevier B V, 2025)
An in vitro method was developed to test gastric irritation by quantifying the secretion of interleukin-8 (IL-8) by human intestinal epithelial cells Caco-2 after incubation with gastric digesta of emulsion gels containing capsaicinoids (CAP) obtained from simulated dynamic gastric digestion. The emulsion gel structure was modified using different emulsifiers: whey proteins versus Tween 80. Results indicate that both the CAP and Tween 80 molecules were proinflammatory to Caco-2 cells and stimulated cells to produce IL-8. Gastric digesta from CAP-loaded Tween 80 emulsion gel stimulated significantly more IL-8 production than CAP-loaded whey protein emulsion gel, possibly because of the presence of Tween 80 and also, because more CAP molecules were released from Tween 80 emulsion gel during gastric digestion. Tween 80 emulsion gel had a loose structure; it was easily broken down into smaller pieces and had large amounts of oil droplet liberation from the protein matrix, which would promote the release of CAP molecules, leading to higher IL-8 production. On the other hand, whey-protein-coated oil droplets had strong connections with surrounding protein matrix and were well protected during gastric digestion; the release of CAP molecules was much less. This study suggests that by modifying the structure of the foods, the gastric digestion behaviour can be modified, which would affect the release behaviour of CAP molecules and influence gastric irritation / inflammation.
Keywords: Emulsion gel; Capsaicinoid; Whey protein; Tween 80; Interleukin-8